Penerapan Metode Profile Matching Pada Proses Seleksi Rekrutmen Pegawai Berdasarkan Faktor Kompetensi Spencer - Rani Purbaningtyas (Jurnal Teknologi Informasi dan Terapan, 2021)
One of the keys to the company's success is how to place the right people in the right positions. For this reason, the recruitment selection process plays a significant role. This study applies the Profile Matching method to the employee recruitment selection process for the marketing director position. The prerequisites for occupying the position of marketing director are based on 20 Spencer competency factors divided into 6 competency groups with varying weights. The Spencer competency groups used along with the weight variations are Achievement and Action (AA) – 30%, Helping and Human Service (HHS) – 5%, Impact and Influence (IMIN) – 10%, Managerial (MNG) – 30%, Cognitive (COG) – 15% and Personal Effectiveness (PE) – 10%. The results showed that the employee on behalf of Sigit Hernowo was the strongest candidate for the Marketing Director position with a score based on the Spencer competency factor of 4.46 points.